Vegetable grafting: a scientific innovation to enhance productivity and profitability of tomato growers under climate change - Khopade, Rohan Y.; Sawargaonkar, Gajanan L.; Rakesh, S.; Davala, Moses Shyam; Kishore K. K.,; Siddam, Yeshwanth; Singh, Ramesh; Jat, Mangi Lal (Frontiers in Agronomy, 2025)
IntroductionVegetable grafting is a recent innovation in vegetable cultivation that has a great potential for enhancing crop productivity and profitability under climate change scenarios, besides its potential to reduce the cost of cultivation.MethodsThe present strategic research focused on assessing the performance of grafted and non-grafted tomato cultivars (PHS-448 & Sahoo) in Naturally Ventilated Polyhouse (NVPH) and open field (OF) conditions.Results and discussionThe results revealed that grafted tomatoes expressed significantly (p<0.05) higher values of growth parameters, i.e., leaf area and chlorophyll content, contributing to significantly higher total yield over non-grafted tomatoes. The grafted tomato cultivars, viz, PHS-448 and Sahoo, recorded an increased total yield of 36.65% and 46.7% respectively compared to the non-grafted ones. Growing grafted tomatoes under NVPH conditions increased yields by 63.79% due to an increase in pickings (by 3 to 5 times) compared to non-grafted tomatoes grown under open field conditions. The system productivity followed similar yield trends and revealed significant (p<0.05) variation across all picking days. The profitability analysis (gross and net monetary returns and benefit-cost ratio) showed that grafted combinations grown under NVPH are more profitable than the open field conditions and non-grafted ones, grown under both conditions. The multiple regression analysis revealed a strong correlation (R2= >80) of yield with plant height, middle leaves chlorophyll, and leaf area, irrespective of the grafted and non-grafted combinations. The present investigation concluded that cultivating grafted tomatoes helps farmers achieve maximum productivity and profitability in both NVPH and open field conditions. However, a proper policy framework is necessary to promote and scale up grafted vegetable technology to enhance the profitability of vegetable growers in climate change scenarios.